Evaluation and comparison of the ability of three industrially relevant adsorbents to remove alcohol contaminants from an alkane solvent - Groenewald, Jomare (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.